A systematic review of medicinal plants and herbal products' effectiveness in oral health and dental cure with health promotion approach - Sara Amanpour; Mahsa Akbari Javar; Zohreh Sarhadinejad; Mohammadmahdi Doustmohammadi; Masoud Moghadari; Zarrin Sarhadynejad (Wolters Kluwer Medknow Publications, 2023)
Medicinal plants and herbal drugs are being used increasingly as part of primary health care in most parts of the world. As important adjunctive and alternative treatments for oral health care, herbal products' use may continue to increase and become more widespread. The objective of this study is to present a comprehensive systematic review of the current published literature on the effectiveness of medicinal plants and herbal products employed to improve oral health in adolescents with a health promotion approach. The systematic review was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The keywords "herbal medicine," "herbal extract," "herbal supplements," "plant extract," "natural drug," "pulpitis," "dental caries," "oral viral diseases," and "abscess" were used in combination with the Boolean operators OR and AND. PubMed, Embase, Scopus, and Web of Science were searched. Quality assessment of the included studies was performed using the Cochrane Handbook for Systematic Reviews of Interventions. The search yielded 49 original research studies. A total of 22 studies had low or unclear risk bias. The geographical distribution of included studies was primarily concentrated on western countries. Overall, studies reported herbal product users' age, ranging from young adults aged 18 years to elderly people aged 75 years or older. Most studies reported multiple compounds, including herbal drugs and herbal extracts. Chamomile and Aloe vera were the most frequently reported herbal compounds. The most commonly described herbal products to treat oral diseases were gels, mouth rinses, and pastes. The studies included a range of people with oral diseases, including periodontal and gingival diseases, recurrent aphthous stomatitis, oral lichen planus, and oral candidiasis. Herbal product interventions were found to be effective and safe alternatives for oral health care. One of the most important goals of the World Health Organization (until 2015) is the oral health index, so it is important that dental services be followed up more seriously. Considering the problems in reaching this goal of the World Health Organization in our country, herbal products have the ability to improve clinical oral health outcomes in adolescents. Limited adverse side effects indicate the overall safety of these treatments for a wide range of oral diseases. Therefore, the use of medicinal plants as well as alternative medicine is one of the useful methods in achieving this important goal of public health.